The value of public art in landscape architecture - Strydom, Gerrit (School of Architecture, Planning and Geomatics, 2014)
To design spaces for public art has become an increasingly difficult exercise due to the constant shifts in the public's social behaviour and attitude towards art. This is exacerbated by the fact that the discipline of art is so unique and diverse it is almost impossible to find a commonly applicable definition. Although these challenges sound daunting, it provide opportunities for creative thinking and unique design solutions. This dissertation is in response to a brief received from the City of Cape Town concerning public art and public space, this brief will be mentioned in detail later. Responding to this brief the dissertation deals with issues of art in public spaces and provides guidelines on how to design these spaces to compliment and celebrate artworks. The document will set up a framework for identifying and designing spaces for public art. The process is through an analysis in the form of a site selection criteria and a spatial selection matrix. Thereafter a set of design guidelines will be drafted and will provide the basis for the design. Finally a design proposal will be executed and complemented by an Environmental Art installation. The emphasis of the dissertation would be to illustrate how art in public space enrich and activate our built environment.